A new deal for southeastern archaeology - Lyon, Edwin A. (Book collections on Project MUSE., 1996)
This comprehensive study provides a history of New Deal archaeology in the Southeast in the 1930s and early 1940s and focuses on the projects of the Federal Emergency Relief Administration, the Civil Works Administration, the Works Progress Administration, the Tennessee Valley Authority, the National Park Service, and the Smithsonian Institution. Utilizing primary sources that include correspondence and unpublished reports, Lyon demonstrates the great importance of the New Deal projects in the history of southeastern and North American archaeology. New Deal archaeology transformed the practice of archaeology in the Southeast and created the basis for the discipline that exists today. With the current emphasis on curation and repatriation, archaeologists and historians will find this volume invaluable in reconstructing the history of the projects that generated the many collections that now fill our museums.